2011
DOI: 10.1179/1743281211y.0000000018
|View full text |Cite
|
Sign up to set email alerts
|

Application of fractal theory on raceway boundary in COREX melter–gasifier model

Abstract: The raceway has been studied extensively both theoretically and experimentally. In this study, particle velocity contours have been developed to define the raceway boundary. The raceway boundary is coarse and fragmentised, but all of the previous studies are based on Euclidean geometry, which regard the dimension of the raceway as an integer. In this paper, the fractal method of calculating raceway size, which describes the boundary with extremely irregular or fragmented characteristics, is on the data from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[5][6][7] According to the practical operation, it has been found that the quantity and quality indexes of COREX process are directly determined by the shaft furnace operation. [8][9][10][11] Although the role of shaft furnace plays is similar with that of lump zone in blast furnace, there are some differences existed between them in terms of gas composition and distribution, as well as burden distribution, which is of significant importance for shaft furnace. 1,12) Many researchers including the authors pay much attention to burden distribution in blast furnace numerically and experimentally, [13][14][15][16][17] while few researchers studied burden distribution in COREX shaft furnace for its short history and few instruments.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] According to the practical operation, it has been found that the quantity and quality indexes of COREX process are directly determined by the shaft furnace operation. [8][9][10][11] Although the role of shaft furnace plays is similar with that of lump zone in blast furnace, there are some differences existed between them in terms of gas composition and distribution, as well as burden distribution, which is of significant importance for shaft furnace. 1,12) Many researchers including the authors pay much attention to burden distribution in blast furnace numerically and experimentally, [13][14][15][16][17] while few researchers studied burden distribution in COREX shaft furnace for its short history and few instruments.…”
Section: Introductionmentioning
confidence: 99%
“…The physical experimental results reported in an earlier paper by the present authors show that the particles in raceway can make rotation under the condition without chemical reactions and particles consumption [25] . In order to analyze the particles velocity further, the velocity vectors of particles around the tuyere are displayed alone, as shows in Fig.…”
Section: Calculated Resultsmentioning
confidence: 85%
“…Based on a real COREX melter-gasifier and its physical model used by the author's research group [25] , are not considered. The gas phase was considered to be incompressible and iso-thermal.…”
Section: Calculation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,[16][17][18][19][20][21][22] There are few numerical simulations relating to the shaft furnace, which also plays an important role in the practical operation of the whole COREX process. [23][24][25][26] Li et al 27 studied the characteristics of binary size burdens' movement in the COREX shaft furnace based on the discrete element method (DEM). They then verified and calibrated a DEM simulation with experiments using yellow rice and soybean with respect to burden distribution and profile.…”
Section: Introductionmentioning
confidence: 99%